Minding the GAP: An overview of five years of Education for Sustainable Development (ESD) projects under the Global Action Programme (GAP) within Regional Centres of Expertise (RCEs) on ESD - Vaughter, Philip; Noguchi, Fumiko; Li, Shengru (Frontiers in Sustainability, 2022)
Research on Regional Centres of Expertise (RCEs) on Education for Sustainable Development (ESD) has focused on how multi-stakeholder and cross-sectoral partnerships can work to enable ESD projects, with a particular focus on how higher education institutions could effectively collaborate with community partners. However, much of this research has focused on how partners worked together (for example, what governance and coordination structures allowed higher education institutions to effectively collaborate with partners) without as much focus of investigation on what activities RCEs were working on. While diverse and compelling research on RCEs already exists, much of this research falls into conceptual theory building or case studies of individual RCE activities. In this article, an overview and analysis of activities from RCEs around the globe is offered to provide some trend analysis for topics and modalities of ESD projects conducted during the Global Action Programme (GAP) on ESD which ran from 2015-2019. This analysis can serve as record of where the Global RCE Network has been over these five years, where it is now, and where it may wish to go in the future.